The Effect of Service Quality, Perceived Value, and Customer Satisfaction on Loyalty and Word of Mouth (WOM) - Nurul Oktaviani; Puspita Chairun Nisa (Lafadz Jaya Publisher, 2024)
The main objective of this research is to fill the knowledge gap in service quality from the perspective of customer satisfaction, perceived value, customer loyalty, customer satisfaction and Word of Mouth (WOM) so that this research is expected to contribute to the scientific level of marketing management by developing a theoretical understanding that both regarding the variables studied and it is hoped that it can also provide positive managerial implications for the implementation of marketing strategies in the service sector, especially banking, in increasing customer satisfaction. The sampling method used in this research is non-probability sampling with purposive sampling technique. Data collection was carried out by distributing online questionnaires to 145 BRI customer respondents domiciled in DKI Jakarta aged 18 - 60 years and who had carried out direct banking transactions at the bank at least twice in the last 3 months. The analytical method used is Structural Equation Modeling (SEM) with the Partial Least Square (PLS) technique using statistical software. The results can be concluded that service quality can influence customer satisfaction in using BRI bank. The perceived value factor also drives customer satisfaction. Customer satisfaction can influence customer loyalty to use BRI bank and customer loyalty can influence Word of Mouth (WOM) of BRI bank customers. This certainly benefits the business owner and creates company success in the long term.